Chapter Traiettorie tecno-economiche - Lombardi, Mauro (Studi e saggi, 2021)
Here six techno-economic trajectories are discussed in light of global challenges and the great changes that are taking place in the techno-scientific and social world: digitization of socio-economic processes, smart specialization, environmental sustainability and systemic resilience, knowledge intensive activities, health topics dealt with IA techniques, bio-economy and agri-food. For each trajectory focus area, actors and indicators are proposed.